Patterns of Change in Approaches to Learning and Their Impact on Academic Performance Among Medical Students: Longitudinal Analysis. Issue 2 (15th March 2021) - Piumatti, Giovanni; Abbiati, Milena; Gerbase, Margaret W.; Baroffio, Anne
Abstract: Theory: Several medical education studies suggest that deep approaches to learning (DA) are associated with better academic performance, whereas surface approaches (SA) are associated with worse academic performance. However, no study has assessed how these approaches change at the individual level during undergraduate medical training and how these trajectories contribute to academic performance. We assessed individual patterns of change in learning approaches throughout five years of medical training to determine whether and how DA and SA evolve during the curriculum and whether initial levels and rates of change predict performance in Year 5. Hypotheses: We hypothesized that (1) medical students have a higher preference for DA in comparison with SA; (2) these preferences change along the medical curriculum; and (3) DA predicts better academic performance. Method: Participants were 268 Geneva medical students (59% female) who completed the revised two-factor study process questionnaire in Years 1, 2, 3, and 5 of their 6-year curriculum. Student academic performance was registered in Year 5. Multivariate latent growth modeling was used to assess individual trajectories in learning approaches and test their associations with performance in Year 5. Results: Medical students were inclined to use DA rather than SA. Nevertheless, from Year 2 onward their use of DA decreased while their use of SA increased. Students with higher initial levels of DA tended to have lower initial levels of SA. Moreover, increases in SA were significantly associated with decreases in DA. However, only initial levels of DA and non-repeater status in Year 1 were positive and significant predictors of academic performance in Year 5. Conclusions: Although students tended to use DA rather than SA when entering medical school, their preferences for DA tended to decline throughout medical training while increasing for SA. Learning approaches during early study years, characterized by engagement and meaningful learning, predicted later academic performance. DA should be promoted during the early years of medical studies to foster student learning and to improve academic performance.